Revitalizing the Estrada do Paraibuna: Exploring Sustainable and Regenerative Tourism Dynamics - Isabel Vaz de Freitas; Rodrigo Meira Martoni (Heritage, 2025)
Cultural heritage reflects accumulated memories, generational practices, and esthetic and cultural ideologies that shape identities. The inherent diversity and uniqueness of these identities define heritage elements, which, however, remain fragile, non-renewable, irreplaceable, and vulnerable. In regions affected by the significant devastation caused by contemporary socio-economic activities, policies often neglect the intrinsic historical and heritage value(s). The historical landscapes with tourism potential that experience decline, degradation, and destruction need even more protection and policies to aid their regeneration and preservation. This study seeks to develop a comprehensive framework for preserving a highly endangered historical road, along with its invaluable monuments and cultural landscapes, as a means to stimulate regional revitalization. The methodological approach relies on observation, field work, and semi-structured interviews to provide a comprehensive historical overview of the Estrada do Paraibuna (Paraibuna Road). This region has suffered significant degradation of its historical and natural assets as a result of intensive resource exploitation. This study underscores the heritage elements with strong tourism potential along the route between Ouro Preto and Barbacena, while underlining the critical need to combat landscape degradation. This study pursues to create a shared vision rooted in promoting sustainable practices that leverage natural and cultural resources, safeguard local culture, and encourage community collaboration in regenerative efforts.